(untitled) (Journal of Parents and Teachers, 2014)
A list of films that follow a teacher as the main character is proposed; these present aspects of interest regarding the figure of the teacher, the students, the parents of the students, etc. The films show, for example, teenagers who manifest an incorrect behavior (a problematic and undisciplined group in particular) and teachers who show great professionalism and humanism. At the end of the article there is an extensive list of films with themes and characters from the world of teaching in the cinema.